Animal and vegetable fats and oils. Determination of fatty-acid-bound chloropropanediols (MCPDs) and glycidol by GC/MS. Method using acid transesterification and measurement for 2-MCPD, 3-MCPD and glycidol Part 3, (3rd February 2022) - British Standards Institution,
No abstract available